61=42-13

Simple and best practice solution for 61=42-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 61=42-13 equation:


Simplifying
61 = 42 + -13

Combine like terms: 42 + -13 = 29
61 = 29

Solving
61 = 29

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -231=-4x+5(3x-22) | | 6-5i/-2i | | 15-3(4x+6)=11-4x | | 3(9c+2)= | | (5/9)^2 | | 10sinx=-5 | | -5x1/5-7 | | 3x+4(6x+11)=206 | | 6x-9=2x+11 | | -2x-3(x+17)=-91 | | 10y+7y=34 | | -x^2+6x=8 | | 4(7x)= | | 3(8x-9)=50 | | 2(3x+5)=22+5x-3x | | (3u-4)(6+u)=0 | | (5/9)^-2 | | 80=2x+4(-3x-10) | | 14x-47=58+11x | | -4log(2x+5)+3=3.2 | | 2x+1=[x-3] | | 13x-108=36+7x | | -12=5x+17 | | 12x^3-44x^2=-49x+15 | | x^6-9i=0 | | -76+x=68-3x | | -10(5)= | | 4+2(x-1)=6 | | 4x^2/7y^2_21xy^2/20x^4 | | y=(2x-3x+3)4 | | -173-12x=67-2x | | ×=m•3/m÷4 |

Equations solver categories